2017
DOI: 10.1590/1983-21252017v30n130rc
|View full text |Cite
|
Sign up to set email alerts
|

Impact Injury Diagnosis in Mango Through Starch Degradation Index

Abstract: -This study aimed to evaluate the use of starch degradation index (SDI) in the diagnosis of areas of impact injuries in 'Tommy Atkins' mango, in different maturation stages. The experiment layout was a fully randomized factorial design (5 x 2), represented by five maturation stages and two handlings, with and without impact, with four replicates. SDI was determined through a subjective scale of scores indicating mango pulp darkened areas by reaction with iodine-potassium iodide solution. Subsequently, these sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Mechanical damage in fruits and vegetables is the rupture of the cellular structure caused by mechanical interactions such as impact, cutting, abrasion, and compression. Many studies found in the literature (Li, 2013;Tezotto et al, 2011;Sousa et al, 2017;Komarnicki et al, 2016;Stropek & Golacki, 2013;Fadiji et al, 2016) carried out analyses in the laboratory and related the physiological behavior observed with the applied force or tension as the final objective.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical damage in fruits and vegetables is the rupture of the cellular structure caused by mechanical interactions such as impact, cutting, abrasion, and compression. Many studies found in the literature (Li, 2013;Tezotto et al, 2011;Sousa et al, 2017;Komarnicki et al, 2016;Stropek & Golacki, 2013;Fadiji et al, 2016) carried out analyses in the laboratory and related the physiological behavior observed with the applied force or tension as the final objective.…”
Section: Introductionmentioning
confidence: 99%